[OP.1A.12] BRACHIAL-ANKLE PULSE WAVE VELOCITY IS RELATED TO THE SEVERITY RATHER THAN THE PRESENCE OF CORONARY ARTERY DISEASE IN THE YOUNG AND MIDDLE-AGED. (September 2017) - Ohno, Y.; Okada, S.; Nakagomi, A.; Shoji, T.; Kobayashi, Y.
Abstract : Objective: Brachial-ankle pulse wave velocity (baPWV) is a marker of arterial stiffness and is technically more feasible as compared to carotid-femoral pulse wave velocity. Previous reports have shown that baPWV is associated with presence and severity of coronary artery disease (CAD) assessed by invasive coronary angiography (CAG) in older subjects. On the other hand, in young and middle-aged adults, baPWV was only demonstrated to be associated with coronary calcium assessed by computed tomography. There are no studies examining relationship between baPWV and CAD assessed by CAG in this population. The aim of this study was to determine the association between baPWV and both presence and severity of CAD assessed by CAG in young and middle-aged adults. Design and method: We enrolled 117 patients under the age of 65 who measured baPWV and underwent elective CAG for suspected CAD. Significant CAD was defined as one or more stenosis over 50%. To evaluate severity of CAD, we measured SYNTAX and Gensini scores. Using univariate and multivariate logistic regression analysis, we evaluated the contribution of baPWV for the presence of significant CAD. In patients with CAD, we also assessed the association between baPWV and both SYNTAX and Gensini scores using linear and multiple regression analysis. Results: In univariate logistic regression analysis, baPWV was associated with presence of significant CAD in univariate logistic regression analysis (Odds Ratio (OR) 1.16, [95% Confidence Interval (95% CI) 1.02–1.33], p = 0.03). In multivariate analysis, the association was canceled after adjusting traditional coronary risk factors. In univariate linear regression analysis, baPWV was associated with both Gensini and SYNTAX scores (Gensini: coefficient 2.19[95% CI 0.17–4.21], p = 0.03, SYNTAX: coefficient 1.09[95% CI 0.34–1.83], p = 0.01). In multiple regression analysis, baPWV remained significantly related to both severity scores (Gensini: coefficient 3.52[95% CI 0.06–7.00], p = 0.046, SYNTAX: coefficient 1.85[95% CI 0.65–3.04], P < 0.01). Conclusions: In young and middle-aged population, increased arterial stiffness assessed by baPWV is associated with the severity, rather than the presence, of CAD.